Design and content validity of an instrument for analysis of teacher identity - Petkova-Gueorguieva, Marieta (2025)
Objective: Design a questionnaire for the analysis of teacher identity and validate its content. Methods: theoretical review of the concepts for the creation of the questionnaire: educational trends and norms and the method of expert judgment for the evaluation of the items based on pertinence, relevance, clarity and sufficiency. The statistical indices of content validity were used Aiken's V coefficient and Content Validity Index (CVI) of Lawshe (1975) modified by Tristán-López 2008. Results: The concept of teaching identity was defined as “the teacher's self-reflection about their teaching work and relationship they establish with their immediate, institutional and work context”, and the specifications for the use of the questionnaire were developed. The wording of the 33 items was improved and the final version of the instrument after the evaluation by the expert judges and the quantitative analysis left with 6 general questions and 40 specific reagents, distributed in three dimensions: disciplinary 5 reagents, didactic pedagogical 23 and institutional and work context 12 reagents. Conclusion: It was concluded that the design and content evaluation of the instrument contributed to the evidence of validity of the instrument for analysis of teacher identity